2020
DOI: 10.1111/cen.14202
|View full text |Cite
|
Sign up to set email alerts
|

Solid pseudopapillary tumour should be part of differential diagnosis of focal pancreatic lesions with increased 18F‐FDOPA uptake

Abstract: Objective To assess the specificity of increased 18F‐dihydroxyphenylalanine (18F‐FDOPA) uptake in patients who underwent PET/CT for suspicion of isolated pancreatic neuroendocrine tumour (pNET). False‐positive results mimicking a pNET have been investigated. Material and methods Carbidopa‐assisted 18F‐FDOPA PET/CT scans performed in patients with suspicion of localized pNET were retrieved. Only patients with a definitive diagnosis were retrospectively included. When available, the histopathological result afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The 18 F-FDOPA PET-positive/SRS-negative lesions might be the SPTs. However, these should be verified in a large cohort [ 21 ]. EUS-FNB might be another promising diagnostic tool for distincitng SPTs from PNENs [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 18 F-FDOPA PET-positive/SRS-negative lesions might be the SPTs. However, these should be verified in a large cohort [ 21 ]. EUS-FNB might be another promising diagnostic tool for distincitng SPTs from PNENs [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, both SPTs and cystic endocrine tumors have the same features, such as areas of cystic change, enhancing components, and well-defined contours [20]. Although positron emission tomography/computed tomography (PET/CT) is widely used in the diagnosis of malignant tumors and pancreatic disease, there are very few studies that evaluated the accuracy of PET/CT in the diagnosis of SPTs [21][22][23]. François et al reported that 18 F-FDOPA PET/CT was a promising approach for the diagnosis of pNENs and SPTs.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 ) In order to estimate the potential impact of modified steroidogenesis on UFC measurements, 2 groups of samples were studied. Group As underlined by Oβwald et al, 5 In conclusion, a fast and reliable method for UFC measurements improves patient care, allows day-to-day treatment adjustment and therefore shortens the length of hospital stay.…”
mentioning
confidence: 87%
“…When available, mainly in specialised centres, molecular imaging with [ 18 F] F-DOPA can be applied using labelled analogue for the GLP-1 receptor [ 11 C]C-methionine [93]. Imaging with [ 18 F] F-DOPA, in accordance with the 2017 European Association of Nuclear Medicine (EANM) guidelines, is not recommended in PanNET due to the potential risk of false positives in non-neuroendocrine pancreatic neoplasms, such as pancreatic pseudopapillary tumour, and pancreatic serous cystadenoma [94,95].…”
Section: Guidelinesmentioning
confidence: 99%